H2S oxidation by nanodisc-embedded human sulfide quinone oxidoreductase - Landry, Aaron P.; Ballou, David P.; Banerjee, Ruma (The Journal of biological chemistry, 2017)
Buildup of hydrogen sulfide (H2S), which functions as a signaling molecule but is toxic at high concentrations, is averted by its efficient oxidation by the mitochondrial sulfide oxidation pathway. The first step in this pathway is catalyzed by a flavoprotein, sulfide quinone oxidoreductase (SQR), which converts H2S to a persulfide and transfers electrons to coenzyme Q via a flavin cofactor. All previous studies on human SQR have used detergent-solubilized protein. Here, we embedded human SQR in nanodiscs (ndSQR) and studied highly homogenous preparations by steady-state and rapid-kinetics techniques. ndSQR exhibited higher catalytic rates in its membranous environment than in its solubilized state. Stopped-flow spectroscopic data revealed that transfer of the sulfane sulfur from an SQR-bound cysteine persulfide intermediate to a small-molecule acceptor is the rate-limiting step. The physiological acceptor of sulfane sulfur from SQR has been the subject of controversy; we report that the kinetic analysis of ndSQR is consistent with glutathione rather than sulfite being the predominant acceptor at physiologically relevant concentrations of the respective metabolites. The identity of the acceptor has an important bearing on how the sulfide oxidation pathway is organized. Our data are more consistent with the reaction sequence for sulfide oxidation being: H2S → glutathione persulfide → sulfite → sulfate, than with a more convoluted route that would result if sulfite were the primary acceptor of sulfane sulfur. In summary, nanodisc-incorporated human SQR exhibits enhanced catalytic performance, and pre-steady-state kinetics characterization of the complete SQR catalytic cycle indicates that GSH serves as the physiologically relevant sulfur acceptor.